Magnetoelectric coupling at the NiFe2O4/PZT (001) interface: A density functional theory investigation. (March 2020) - Tamerd, M. Ait; Abraime, B.; Lahmar, A.; El Marssi, M.; Hamedoun, M.; Benyoussef, A.; El Kenz, A.
Abstract: Magnetoelectric (ME) coupling at the Ferrimagnetic/Ferroelectric NiFe2 O4 /PbZr0.5 Ti0.5 O3 (001) (NFO/PZT) heterostructure have been investigated using first-principles within density-functional theory in the framework of GGA + U. The (Zr0.5 Ti0.5 )O2 -terminated and PbO-terminated PZT surfaces are considered at the NiFe2 O4 /PZT interface (NFO/ZTO and NFO/PbO). Based on the interfacial separation work, our first-principle calculations predict that the (Zr0.5 Ti0.5 )O2 -terminated PZT surfaces is energetically more favorable than the PbO-terminated PZT surfaces at the NiFe2 O4 /PZT interface. Moreover, it is found that the magnetoelectric coupling in this system arises from the interface bonding and the electronic origin of the large magnetoelectric coupling at NFO/ZTO interface is due to the hybridizations of orbitals of interface Ni, Fe, T, Zr, O atoms. In addition, the maximum magnetoelectric coefficient of α = 3.15 ×   10 − 10 G.cm/V has been achieved for (Zr0.5 Ti0.5 )O2 -terminated PZT surfaces in NiFe2O4/PZT interface. Highlights: NiFe2 O4 /PbZr0.5 Ti0.5 O3 (001) heterostructure was investigated using first-principles. Ferroelectric, magnetic and magnetoelectric properties of NiFe2 O4 /PbZr0.5 Ti0.5 O3 heterostructure have been calculated. A maximum magnetoelectric coefficient of α = 3.15 ×   10 − 10  G.cm/V has been achieved for NFO/ZTO in NiFe2O4/PZT interface.